PRESTASI KERJA KARYAWAN DAN VARIABEL YANG MEMPENGARUHI, SUATU TINJAUAN TEORITIS - M. Rapi Anci (Jurnal Bisnis dan Kewirausahaan, 2016)
Competent human resources is one of the important variables to improve the performance, as a driving force towards the achievement of the performance of an organization or business entity which is engaged in the production of goods and services in the field of (service). Factors human resources should receive top priority in its management so that organizations can achieve the goals that have been set previously. Companies need a Human Resources productive. Human Resources productive not only carry out the work based on the tasks that have been assigned to him, but rather try to improve work performance or float.